Conciliação como forma de solução de conflito no direito: teoria dos jogos aplicada à conciliação trabalhista - Salgado, Priscila Mascarelli (2009)
The development of this study had as main objective demonstrate that through the Theory of Games can explained the conciliation as a solution of the conflict in Labor Law. The types of games from this theory allow analyze the alternatives between the parts during the conciliation, thus facilitating the understanding of the behavior of individual decision making. First social conflict will be studied, after the conflicts modes, their languages, communications, then approximate conflict and the law. Analyzed the social conflict, are then taken to their solution through the law using one of these ways of resolving conflict: self-tutelage, selfcomposition or hetero-composition. Within the hetero-composition is conciliation, which will be explained in each area of law: Civil, Criminal and Labor. After this study of law, the work will treat the Theory of Games of John von Neumann and Oskar Morgenstern. Show the games modes, their actions and strategies. This will cross the law information with the Theory of Games and then explained the possible alternatives of choices of each party / player during the conciliation